1995
DOI: 10.1021/cm00049a008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polyaniline Derivatives: Poly(2-alkoxyanilines) and Poly(2,5-dialkoxyanilines)

Abstract: A series of 2-alkoxyanilines and 2,5-dialkoxyanilines with alkyl chains containing n = 1, 2,4, and 6 carbon atoms have been electropolymerized in acidic conditions and characterized by several techniques. The corresponding neutral polymers were found to be soluble in chloroform and tetrahydrofuran. On the other hand, chronoamperometry experiments have shown that the presence of long alkoxy groups {n -4 and 6) decreases the rate of polymerization, giving materials with a lower degree of polymerization. Electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(89 citation statements)
references
References 0 publications
1
86
0
2
Order By: Relevance
“…Previous studies revealed that introducing mono alkyl or alkoxy substituents on the ortho position of the phenyl ring resulted in an increase of solubility, and at the same time, a decrease in conductivity [20][21][22][23][24][25] . However, the presence of 2,5-dialkoxy substituted on the phenyl rings resulted in an enhanced conductivity 12 . Recently, 2,5-dimethoxyaniline (DMA) has been reported to produce soluble poly(2,5-dimethoxyaniline) (PDMA) with a conductivity similar to polyamine [26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies revealed that introducing mono alkyl or alkoxy substituents on the ortho position of the phenyl ring resulted in an increase of solubility, and at the same time, a decrease in conductivity [20][21][22][23][24][25] . However, the presence of 2,5-dialkoxy substituted on the phenyl rings resulted in an enhanced conductivity 12 . Recently, 2,5-dimethoxyaniline (DMA) has been reported to produce soluble poly(2,5-dimethoxyaniline) (PDMA) with a conductivity similar to polyamine [26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the use of organic materials, particularly conducting polymers, has received more attention because of their fast response, low cost, good processibility, and color tailor ability 9 . Polyaniline, discovered in 1982 by Letheby 10 , is one of the most studied conducting polymers and has been used in many applications due to their environmental stability, low cost of fabrication, and unusual electrical and optical properties [11][12][13][14][15] . In addition, polyaniline exhibits electrochromic effects, from pale yellow to green to blue-velvet [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Note that the N−Li coordination in 4 renders the C ipso centers in the LiR N Cu unit stereogenic (either S or R configuration). 37,49,76 This affects the assembly process, providing an enantiomeric pair of one diastereoisomer, either SSSS or RRRR; the presence of the Me 2 NCH 2 renders the assembly process stereoselective ( 13 C and 7 Li NMR and cryoscopy measurements). The use of a chiral (either S or R configuration) o-Me 2 NCHMe grouping makes the LiR N Cu unit diastereoisomeric.…”
Section: ■ the Start Of My Journey In Organocopper Chemistrymentioning
confidence: 99%
“…The use of Ph-NCN allowed for the synthesis of the corresponding (rare at the time) organo-Ni(III) compounds. These NCNpincer-d 7 (18). 81 Finally, the stable organocopper(II) and -(III) compounds are the direct result of a selective C−H activation process starting from the corresponding arene compound interacting with the appropriate copper salt.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The use of bidentate ligands like phenanthroline [14][15][16][17][18], diamines [19][20][21], amino acids [22][23][24], and 1,3-diketones [25,26] among others [27][28][29][30] has not only met the demands of reliability, mildness, and functional group tolerance but also interesting modern features such as orthogonal reactivity [26]. The applications so far known have been spread over a diverse range of areas from pharmaceutical [31] and natural products [32][33][34] to materials fields [35,36].…”
Section: Introductionmentioning
confidence: 99%